Diversity of morphology, pathogenicity, and host range of Colletotrichum spp. associated with chili anthracnose in East Priangan, Indonesia - IDA HODIYAH; MAMAN SURYAMAN; ELYA HARTINI; ADE H. JUHAENI; BUDI Y. LAKSANA; AISYAH AISYAH; GILANG V. BENATAR (Society for Indonesian Biodiversity, 2024)
Abstract. Hodiyah I, Suryaman M, Hartini E, Juhaeni AH, Laksana BY, Aisyah, Benatar GV. 2024. Diversity of morphology, pathogenicity, and host range of Colletotrichum spp. associated with chili anthracnose in East Priangan, Indonesia. Biodiversitas 25: 533-541. Chilies, in Indonesia, encounter several obstacles that impact their production and quality. Chili production in Indonesia has seen oscillations, partly due to the detrimental effects of anthracnose disease produced by the Colletotrichum fungus species. The disease has a detrimental effect on the quality of fruit, foliage, and plants, resulting in unpredictable yields and significant losses, especially during the rainy season. Although chilies has important economic value in Indonesia, more comprehensive studies are needed on chili anthracnose in the East Priangan area, West Java Province, Indonesia. The purpose of this research was to specifically investigate the incidence of chili anthracnose and to isolate the pathogen responsible for the disease. Colletotrichum isolates were subjected to morphological characterization and pathogenicity tests to assess their virulence. In addition, the research evaluated the possible spectrum of hosts that these isolates might infect in order to determine their effect on other commodities. In East Priangan, chili anthracnose disease was found everywhere with severe disease incidence. Highest disease incidence was recorded in Garut District (100%), and the lowest was in Ciamis District (50.5%). The isolation results showed that a total of 18 diverse isolates were isolated from three chilli species at different altitudes. Macroscopic and microscopic characteristics showed variability, with growth rates ranged from 0.24 to 3.7 mm per day and diverse conidia shapes and sizes. The pathogenicity test confirmed the virulence of 17 isolates, causing symptoms with concave circular wound diameters ranged from 6.88 to 61.08 mm. Host range results demonstrated the pathogenicity of specific isolates to tomatoes, strawberries, and grapes, with strawberries exhibited higher severity levels (28.05 to 56.38 mm lesions). Gaining comprehensive knowledge about the variety and widespread occurrence of chili anthracnose in this particular area is essential for formulating effective measures to minimize its adverse effects on chili cultivation and guarantee the long-term viability of the chili sector in Indonesia. To our knowledge, this is the first study of chili anthracnose in the East Priangan region.